Gli esploratori della Terra (GEOmedia, 2010)
Earth's explorersAs if in the need to underline that much is still to be discovered about our own planet, the Earth Explorers missions of ESA, the European Space Agency, are part of an intense research  programme called Living Planet. We already discussed, see GEOmedia 01/2009, about the first mission, GOCE (Gravity field and steady-state Ocean Circulation Explorer). In this issue, we discuss the state of the SMOS and CryoSat missions, now both operational after being launched in the previous months.